2017
DOI: 10.1111/trf.14288
|View full text |Cite
|
Sign up to set email alerts
|

B cells require Type 1 interferon to produce alloantibodies to transfused KEL‐expressing red blood cells in mice

Abstract: Background Alloantibodies to RBC antigens can cause significant hemolytic events. Prior studies have demonstrated that inflammatory stimuli in animal models and inflammatory states in humans, including autoimmunity and viremia, promote alloimmunization. However, molecular mechanisms underlying these findings are poorly understood. Given that type 1 interferons (IFNα/β) regulate antiviral immunity and autoimmune pathology, the hypothesis that IFNα/β regulates RBC alloimmunization was tested in a murine model. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 54 publications
(121 reference statements)
2
24
1
Order By: Relevance
“…CD64 expression is typically observed in response to IFNγ stimulation of monocytes, and recent in vitro data has shown that IFNα/β suppresses IFNγ responses in macrophages, leading to CD64 downregulation . Although we did not find differences in measured IFNγ levels between responders and non‐responders, our findings in sickle cell patients may be consistent with recent work from our laboratory showing that IFNα/β impacts the ability of a murine transfusion recipient to form RBC alloantibodies to the KEL human blood group antigen expressed on murine RBCs . Taken together, these data suggest that alloimmunized patients with SCD may have higher IFNα/β levels that prevent IFNγ from leading to the same increase in CD64 expression as would be seen in the absence of IFNα/β.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…CD64 expression is typically observed in response to IFNγ stimulation of monocytes, and recent in vitro data has shown that IFNα/β suppresses IFNγ responses in macrophages, leading to CD64 downregulation . Although we did not find differences in measured IFNγ levels between responders and non‐responders, our findings in sickle cell patients may be consistent with recent work from our laboratory showing that IFNα/β impacts the ability of a murine transfusion recipient to form RBC alloantibodies to the KEL human blood group antigen expressed on murine RBCs . Taken together, these data suggest that alloimmunized patients with SCD may have higher IFNα/β levels that prevent IFNγ from leading to the same increase in CD64 expression as would be seen in the absence of IFNα/β.…”
Section: Discussioncontrasting
confidence: 64%
“…Recently, studies in an animal model related IFNα/β and RBC alloimmunization, with exogenous IFNα/β increasing the likelihood of a transfusion recipient becoming alloimmunized. Further, recipients lacking type 1 IFN receptors failed to become alloimmunized . Other cytokine genes also have been shown to be more prevalent in alloimmunized patients with SCD compared to non‐alloimmunized patients …”
mentioning
confidence: 99%
“…Influenza infection induces Type 1 interferons (IFN‐α/β) and NFkB‐inducible cytokines, including tumor necrosis factor‐α) and IL‐6, and influenza has also been shown to activate inflammasomes . Given our recent reports suggesting the importance of IFN‐α/β on RBC alloimmunization, we hypothesized that the mechanism through which influenza regulates RBC alloimmunization in this murine model is at least in part dependent on recipient IFN‐α/β signaling. To investigate this hypothesis, we infected wild‐type C57BL/6 mice or mice lacking IFN‐α1 receptors (IFNAR KO) with influenza and transfused them 3 days later with K1 RBCs.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple studies have also described a close association between RBC alloantibodies and RBC autoantibodies (Dhawan et al , ; Nickel et al , ). Animal studies (Gibb et al , ,b) suggest that a potential unifying hypothesis for the connection between some types of autoimmunity (Crow, ) and alloimmunization may involve type 1 interferon signalling.…”
Section: Discussionmentioning
confidence: 99%